Google Translation readability from Obama Speech (English to Indonesia translation) - Rioni Mulandari; Dhanu Ario Putra; Eli Diana (UNIVED Press, 2020)
The lookup is a descriptive translation learn about focusing on the methods and ideology of translation offigure of speech used in the text of Srimad Bhagavatam into Indonesian. It departed from atranslation paradigm that considered Srimad Bhagavatam as a product, and the have an impact on of the strategies and ideology applied to the readability stage of figure of speech translation contained in Srimad Bhagavatam from English to Indonesian. Thisis a library study and the approach used in accumulating the statistics is observation, by reading the studied text carefully on the sentences that comprise discern of speech. To view the translation readability level, three informants are concerned to entire a questionnaire containing about the readability stage of translation. This study shows that the ideology held by way of the translator is domestication by means of applying communicative technique of translation on most sentences with parent of speech. Keyword: readability, figure of speech, translation